Management systems for nematode control in soybean fields in south‑central Paraná, Brazil - Gardiano-Link, Cristiane Gonçalves; Santana-Gomes, Simone de Melo; Kluge, Elizandro Ricardo; Feksa, Heraldo Rosa; Kluge, Fabiéli Teixeira da Rosa; Dia-Arieira, Claudia Regina (Pesquisa Agropecuaria Brasileira, 2022)
The objective of this work was to evaluate the effects of winter crops and of soybean management systems on Pratylenchus brachyurus and Helicotylenchus dihystera populations, in a naturally infested site, in the south-central region of the state of Paraná, Brazil. The experiment was carried out during two crop years (2017/2018 and 2018/2019). Barley or black oat (winter crops) and soybean (summer crop) were treated with chemical or biological nematicides applied in the furrows or as seed treatment. Nematode reproduction on soybean was evaluated at 45 and 90 days after sowing (DAS). Soybean yield and 1,000-grain weight were also determined. The principal component analysis (PCA) of 2017/2018 showed a positive correlation between P. brachyurus and H. dihystera reproduction with barley/soybean + cadusafos, barley/soybean + abamectin, and barley/soybean + Bacillus spp., at 45 DAS, which shows that these treatments favored initial nematode reproduction. In the 2018/2019 crop year, the untreated barley/soybean, barley/soybean + abamectin, and black oat/soybean + abamectin systems favored the increase of 1,000-grain weight. The chemical control reduced P. brachyurus reproduction in both crop years. Black oat and the treatments with abamectin of winter and summer crops control P. brachyurus and increase soybean yield. However, the results are not conclusive for H. dihystera management.
Keywords: Helicotylenchus dihystera; Pratylenchus brachyurus; biological nematicide; chemical nematicide; winter crop